Transition-Metal-Free N-(o-Halo)arylation of Sulfoximines/Sulfonimidamides - Padma Priya, V. R.; Irfana Jesin, C. P.; Nandi, Ganesh Chandra (Synlett, 2022)
A transition-metal-free novel route to access N-(o-halo)arylsulfoximines/sulfonimidamides is achieved by the reaction of sulfoximine/sulfonimidamide, aryne precursor, and CCl4/CBr4 in the presence of KF/18-crown-6. The in situ generated benzyne intermediate (from silyl aryl triflate) reacts with the nucleophile (sulfoximine/sulfonimidamide) and halide source (CCl4/CBr4) to yield the product in moderate to good yield. The protocol exhibits broad substrate scope. The regioisomers formed from the unsymmetric aryne precursor were separated effectively via column chromatography.
Keywords: aryne precursor; carbon tetrahalide; sulfoximine; sulfonimidamide; transition-metal-free route